Consequences of Lockdown During COVID-19 Pandemic in Lifestyle and Emotional State of Children in Argentina - Fasano, María Victoria; Padula, Marcela; Azrak, María Ángeles; Avico, Ana Julia; Sala, Marisa; Andreoli, María F. (Frontiers in Pediatrics, 2021)
The implications of the coronavirus disease (COVID-19) lockdown measurements and social isolation in children and their parents are still unknown. The aims of this study were to examine the impact of COVID-19 lockdown on emotional state, feelings and lifestyle of children and their parents, to explore the association between parental characteristics and child well-being and to examine whether the impact of lockdown depends on socio-economic status. Parents completed an online survey including data about socio-demographic information, parent and child feelings and lifestyle during lockdown. Logistic regression and correlation analysis were used to establish associations between variables. In total, 814 parents with children between 4 and 11 were included in the study. According to parents, 69.5% of the children showed changes in their emotional state, 55.3% altered their routine and 62.6% showed sleep disorders. Families with lower socio-economic status were more worried about health, shortage of food and household income (p<0.01). Parent and children concern about food/essential items were highly associated [OR (CI 95%) 13.0 (6.81; 26.5), p<0.01]. Adverse children´s emotional state was associated with parental feeling of loneliness (r=0.35) and inversely associated with keeping a routine (r=-0.11). Sleep changes were inversely associated with keeping a routine and having a balcony/garden (r=-0.53 and -0.16). We conclude that lockdown affected emotional state and lifestyle of children and parents, which were strongly related. Routine and positive parental attitude supported children´s well-being. Economic issues were an important concern in families with lower socio-economic status. Our findings can help to promote child health during lockdown.